Engaging stakeholders as a condition of creating social innovations - Jastrzębska, Ewa (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
Nowadays the world is characterized on the one hand by the rapid pace of changes, their unpredictability, restricted resources, multi-dimensional social challenges, and on the other, widely accessible modern technology which has led to the “birth” of social innovations. Social innovation, like every other innovation, is something new, an improved solution. In the case of social innovations their essence is, however, a social element and it is this social element which is also the aim of innovation, and not only its consequence. Social innovations are therefore social, both as regards the aim, nature, scope, process and its effects. This article presents theoretical and empirical considerations on the essence of social innovations and also the role of dialogue with stakeholders in the process of their creation. It is based on a critical analysis of literature on the subject, desk and web research, and also research conducted in selected enterprises
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 464, s. 57-68
Keywords: social innovations; social needs; social relations; stakeholders’ engagement; innowacje społeczne; potrzeby społeczne; relacje społeczne; angażowanie interesariuszy